2010 Canadian Conference on Computer and Robot Vision 2010
DOI: 10.1109/crv.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Imaging as a Way to Classify Cognitive Workload

Abstract: As epitomized in DARPA's 'Augmented Cognition' program, next generation avionics suites are envisioned as sensing, inferring, responding to and ultimately enhancing the cognitive state and capabilities of the pilot. Inferring such complex behavioural states from imagery of the face is a challenging task and multimodal approaches have been favoured for robustness. We have developed and evaluated the feasibility of a system for estimation of cognitive workload levels based on analysis of facial skin temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Thermal cameras are both unobtrusive and able to capture information from multiple users at a distance and at the same time. Previous research has shown that thermal patterns reveal different aspects of our internal states, including affect [24,60], stress [48], and deception [49]. Further, advances in miniaturization and mass production have continuously brought down the prices of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal cameras are both unobtrusive and able to capture information from multiple users at a distance and at the same time. Previous research has shown that thermal patterns reveal different aspects of our internal states, including affect [24,60], stress [48], and deception [49]. Further, advances in miniaturization and mass production have continuously brought down the prices of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…The finding indicates there is a correlation between facial thermal features and affective states. Stemberger et aI., [7] reported on the development of Augmented Cognition program for next generation avionics suites with capability of measuring or classifying cognitive workload of the pilot. They concluded that the change in subjective and objective workload generated significant facial thermography signatures that could be acquired by thermal camera and further analyzed by the system.…”
Section: A Overview Of Infrared Imagingmentioning
confidence: 99%
“…Wilson and Russell [2003] presented different ways in which the physiological signals are known to change with the state of the operator: heart rate increases, for example, as the cognitive demands on the operator increase, and the rate of eye blinking decreases as the visual demands increases. Mental Workload changes, in particular, have been obtained by recording: cardiac activity [10,22,62], electrodermal response (EDR) and galvanic skin response (GSR) [14,50], eye function (pupil diameter) [9,32], imaging the brain [8,52], and even facial skin temperature [53]. As Mental Workload is a concept, each of these techniques essentially detect the changes in the autonomic nervous systems, which are then used to infer workload levels.…”
Section: Physiological Measuresmentioning
confidence: 99%
“…We used an fNIRS device, which has been shown to be suitable for HCI user study evaluations, but more commercially available devices like the NeuroSky 4 EEG device might be more suitable for day to day feedback. Similarly, even less invasive measures of mental workload could be taken from Heart Rate Variability [24] through smart watches, remotely detected by pupil dilation [33] or facial skin temperature [53] with cameras. Many of these other measures also better detect emotional responses, and perhaps concepts like stress and anxiety, and so might better serve future work on recording both Mental Workload and emotional response.…”
Section: Future Workmentioning
confidence: 99%